Syntactic Rhythm of Political Speeches as a Psycholinguistic Tool of Suggestive Influence - Alla Martynyuk; Alina Ponikaryova (Психолінгвістика, 2018)
This paper addresses the problem of linguistic means of suggestive influence. Suggestive influence is viewed as engrafting into the individuals’ psychic certain ideas, feelings, emotions, or other psychophysiological states bypassing their critical rational thinking. It is stated that suggestion works at the level of structure, specifically, at the level of syntactic arrangement of speech, creating persistent rhythmic-syntactic patterns that grow familiar and build anticipation switching off rationality, and making comprehension subconscious. The study is based on the structural and cognitive analysis of the syntax of Obama’s and Cameron’s political speeches. The cognitive analysis employs the instruments provided by L. Talmy’s FIGURE-GROUND construal. The analysis reveals that the syntax of the analysed political speeches is based on the three structural-semantic patterns of arranging predications: the structural-semantic incorporation, the semantic incorporation and the chain attachment. The structural-semantic incorporation and the chain attachment are underpinned by the linear cognitive scheme of changing the listeners’ focus of attention. The linear scheme is natural for the development of discourse. It sets the prevailing rhythmic-syntactic pattern of a political speech. Since this pattern is predictable, it serves to automatize perception and weaken rational evaluation of the speech content. The semantic incorporation is underpinned by the non-linear cognitive scheme of changing the listeners’ focus of attention. This scheme goes contrary to the natural development of discourse. It breaks the prevailing rhythmic-syntactic pattern and makes the listeners concentrate on what is being said. The change of patterns ensures the listeners’ interest to the speech.